The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/cfp2.1070
|View full text |Cite
|
Sign up to set email alerts
|

Personality, ideology, and money attitudes as correlates of financial literacy and competence

Abstract: This study looked at whether demographics, religious beliefs, political orientation, personality traits, and money attitudes are correlates of financial capability, knowledge and distress. Over 3,500 British participants completed multiple measures online. As hypothesized, demographics, religious beliefs, political orientation, personality traits, and money attitudes each explained unique variance in financial capability, financial knowledge, and financial distress. Regression and correlational results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…It is possible for financial knowledge or overconfidence to be related to other variables. For instance, Fenton‐O'Creevy and Furnham (2020) found that individual demographic factors, money attitudes, personality traits, and ideology were related to financial knowledge. We should be cautious in making causal inferences from our analyses, as we did not attempt estimations that might reduce bias due to potential endogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible for financial knowledge or overconfidence to be related to other variables. For instance, Fenton‐O'Creevy and Furnham (2020) found that individual demographic factors, money attitudes, personality traits, and ideology were related to financial knowledge. We should be cautious in making causal inferences from our analyses, as we did not attempt estimations that might reduce bias due to potential endogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…These four scales were designed to assess attitudes to money (Fenton-O'Creevy and Furnham, 2020, von Stumm et al, 2013. The 16 items are categorized into four scales: money as security (Cronbach's alpha = .65), money as autonomy (Cronbach's alpha = .64), money as power (Cronbach's alpha = .76), and money as generosity (Cronbach's alpha = .64).Example items: "The best thing about money is that it means you can influence others" (power); "I would rather save money than spend it" (security); "The main point of earning money is to feel free and be free" (autonomy); and "I often demonstrate my love to people by buying them things" (generosity).…”
Section: Money Attitudesmentioning
confidence: 99%
“…The determinants of adult financial capability, financial distress, financial knowledge and financial welfare matter, because they affect a person's health and general welfare (Fenton, O'Creevy & Furnham, 2020). There are various measure of financial literacy and well-being (Bruggen et al, 2017;Folk et al, 2019) but many fewer on financial distress.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of credit revolve around whether the debt is paid back on time or at all, or whether an individual has late payments or defaults on the debt (Ozdemir & Boran, 2004). Few papers directly study default or late payment rates in relation to specific psychological factors, so instead for this review a general outcome of financial distress is considered, incorporating over-indebtedness (Almenberg et al, 2016) late repayments, repossessions and bankruptcy (Fenton-O'Creevy & Furnham, 2020). This is perhaps the most important aspect for lenders as borrowers more likely to have these outcomes are riskier prospects.…”
Section: Credit Acquisition/use and Outcomesmentioning
confidence: 99%